HELMINT FAUNA OF SMALL HORN CATTLE OF KARAKALPOGAN AND ON THE SPECIFIC CHARACTERISTICS OF ITS ECOLOGY (Scientific journal of the Fergana State University, 2024)
During 2021-2024, research work was carried out to study helminths of small horned cattle in different regions of Karakalpakstan.  As a result, 37 types of helminths were recorded as parasitism in small horned cattle, of which 34 types were found in sheep and 31 types in goats. 13 types of helminths in sheep and 23 types in goats were identified for Karakalpakstan for the first time. 37 species of helminths parasitizing small cattle belong to 25 genera, 16 families, 9 families, 3 classes and 2 types of fauna. Among the listed helminths, the largest number of species, i.e. 26 species (70.2%) belong to nematodes, 8 species (21.6%) to cestodes and 3 species (8.1%) to trematodes. In Karakalpakstan, biocenotic relationships between small horned cattle and their helminths were studied.